2017
DOI: 10.7717/peerj.2986
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect of dexmedetomidine on paroxysmal sympathetic hyperactivity in severe traumatic brain injury patients who have undergone surgery: a retrospective study

Abstract: BackgroundParoxysmal sympathetic hyperactivity (PSH) results and aggravates in secondary brain injury, which seriously affects the prognosis of severe traumatic brain injury patients. Although several studies have focused on the treatment of PSH, few have concentrated on its prevention.MethodsNinety post-operation (post-op) severe traumatic brain injury (sTBI) patients admitted from October 2014 to April 2016 were chosen to participate in this study. Fifty of the post-op sTBI patients were sedated with dexmede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 49 publications
0
32
0
3
Order By: Relevance
“…However, an entirely persuasive meta-analysis is not possible because of heterogeneity and poorly documented published data (3). There are several limitations of systematic pharmacologic studies: (1) the lack of advice on the distribution and metabolic effects of administration route, form, or dose, (2) few have concentrated on the prevention of PSH in TBI patients, and (3) results may not be generalizable due to heterogeneity of the sample population and the absence of adequate statistical power or long-term follow-up data after discharge (3,19,66,80). In view of the above, the focus of ongoing clinical trials is to increase data reliability through multicenter studies, balancing the effects and side effects of the different medications, thus providing results that are useful in clinical practice (3,4,87).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an entirely persuasive meta-analysis is not possible because of heterogeneity and poorly documented published data (3). There are several limitations of systematic pharmacologic studies: (1) the lack of advice on the distribution and metabolic effects of administration route, form, or dose, (2) few have concentrated on the prevention of PSH in TBI patients, and (3) results may not be generalizable due to heterogeneity of the sample population and the absence of adequate statistical power or long-term follow-up data after discharge (3,19,66,80). In view of the above, the focus of ongoing clinical trials is to increase data reliability through multicenter studies, balancing the effects and side effects of the different medications, thus providing results that are useful in clinical practice (3,4,87).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Widely used in the intensive care unit to alleviate pain and anxiety, maintain the stability of hemodynamics, with less respiratory depression without requirement for mechanical ventilation, easy to wake patients up to judge the consciousness state, can be used as a preventive drug for PSH in TBI patients (66,80,81).…”
Section: Advantagesmentioning
confidence: 99%
“…[24] Previous research on TBI patients treated with either DEX or propofol/midazolam found no significant between-group differences regarding the proportions of patients who met the “probable” or “possible” criteria, but more patients met the “unlikely” criteria in the DEX group compared to the propofol/midazolam group. [25] There have been no studies comparing the effect of DEX vs sufentanil on the alleviation of PSH episodes in TBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine, another presynaptic alpha 2 agonist, has been shown to be effective and in some reports even more effective than propofol in acute attacks [ 18 ]. Tang et al showed that dexmedetomidine can prevent the occurrence of PSH after TBI [ 19 ].…”
Section: Discussionmentioning
confidence: 99%